INVOLVEMENT OF MANAGERIAL FUNCTIONS IN THE FUNCTIONING OF SPECIFIC INDUSTRIAL ORGANIZATIONS – "UNCONVENTIONAL TECHNOLOGIES" - Alin NIOAŢĂ (Fiabilitate şi Durabilitate)
In the sensitive field of unconventional technologies, modern technologies, with another pronounced character of novelty, the consolidation of the market segment of industrial organizations, which acquire these new technologies, the resistance to competition and the gaining of new markets, depend deeply on the manager's ability to adapt to the new realities, to operate unprecedentedly and dynamically in the new competitive framework.For this reason, in the field of Unconventional Technologies ", the new managerial approaches will have to gain substantially in realism, quality and response time.